Repeated participation in hospital smoking cessation services and its effectiveness in smoking cessation: a seven-year observational study in Taiwan - Po-Hsun Yang; Yuan-Shan Chien; Dih-Ling Luh (Archives of Public Health)
Abstract Objective The purpose of this study was to evaluate repeated participation in hospital smoking cessation services and its related factors and to explore the correlation between the frequency of participation and its effectiveness in smoking cessation. This study uniquely follows participants over a seven-year period after the removal of financial barriers, with a maximum charge of TWD 200 (USD 6.4) for cessation medications in Taiwan. Methods A secondary analysis of data from a regional teaching hospital in Central Taiwan was conducted, utilizing the database of the Smoking Cessation Therapy Management Center of Health Promotion Administration and the hospital's documentation from 2013 to 2019. Successful smoking cessation was defined as a non-smoking status at the six-month follow-up stages. Repeat participation was identified through the hospital's smoking cessation logs. Logistic and Cox regression analyses were conducted to meet the study objectives, with all statistical procedures performed on SAS version 9.4. Results In this study, 19.16% of the smoking cessation service users participated repeatedly over a period of seven years. After adjusting for the observation time, the Cox regression analysis showed that those who experienced the side effects of smoking cessation, long-term smokers, and those with a history of disease were more likely to participate again (HR:1.39;1.17;2.60). However, those who smoked heavily, drank alcohol, and failed to quit smoking after previous participation were significantly less likely to participate again (HR:0.59,0.55,0.70;0.89;0.66). Finally, this study found no significant correlation between the frequency of repeated participation and the effectiveness of the last smoking cessation service. Conclusion A certain proportion of smokers repeatedly participate in the same hospital's smoking cessation program, which does not diminish its effectiveness. It is implied that relaxing the limit on the quantity of smoking cessation services subsidies will contribute to overall tobacco harm control efforts.